EFFECTIVENESS OF GROUP COUNSELING WITH SELF MANAGEMENT TECHNIQUES TO REDUCE PROCRASTINATION ACADEMICS FOR STUDENTS 2021 FOK PGRI BANYUWANGI UNIVERSITY: EFEKTIFITAS KONSELING KELOMPOK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGURANGI PROKRASTINASI AKADEMIK PADA MAHASISWA 2021 FOK UNIVERSITAS PGRI BANYUWANGI - ingrid indirasitna; Heribertus Wicaksono; Ratna Wulandari (Program Studi Bimbingan dan Konseling, 2024)
Academic procrastination is a type of procrastination carried out on types of formal tasks related to academic assignments. This research aims to, determine the effectiveness of self-management technique group counseling in reducing the academic procrastination behavior of FOK 2021 University of Banyuwang students. This research uses quantitative methods. This type of research is a quasi-experiment with a nonequlvalent pretest-posttest group design. The research results show that: Tcount on the output shows the number 19.395, this means there is a decline. If t count > t table, then Ho is rejected. Which means 19.395 > 2.015, thus where Ha reads